Solution to 35
Ok, this requires using the identity we proved in class:
[p*cis(a)]*[q*cis(b)]=(pq)*cis(a+b)
Remember that cis(a) means cos(a)+i*sin(a)
so, for polar form, apply the above formula:
12cis(11*pi/12)*(7/2)*cis(pi/4)=42*cis(7*pi/6)
For rectangular form, multiply this out:
42*(cos(7pi/6)+i*sin(7pi/6))=42*(-sqrt(3)/2-i/2)=-21*sqrt(3)-21i
There you go!
[p*cis(a)]*[q*cis(b)]=(pq)*cis(a+b)
Remember that cis(a) means cos(a)+i*sin(a)
so, for polar form, apply the above formula:
12cis(11*pi/12)*(7/2)*cis(pi/4)=42*cis(7*pi/6)
For rectangular form, multiply this out:
42*(cos(7pi/6)+i*sin(7pi/6))=42*(-sqrt(3)/2-i/2)=-21*sqrt(3)-21i
There you go!
0 Comments:
Post a Comment
<< Home